Menjaga Keberlangsungan Usaha Koperasi Taman Wisata Candi Borobudur dan Prambanan Daerah Istimewa Yogyakarta - Wahyudin Wahyudin (E-Coops-Day, 2023)
The Borobudur and Prambanan Temple Tourism Park Cooperative is a fairly large cooperative with assets exceeding 22 billion rupiah and the number of members exceeding 1,000 people. At the time of the Covid-19 pandemic, cooperative business income decreased, especially at that time, the tourism sector was most adversely affected by the closure of several tourism business activities. Seeing these conditions it is important to maintain business continuity and the sustainability of the cooperative's life so that tips, strategies and suggestions are needed for cooperatives.